(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This is the first available study in Muzaffarnagardistrict to examine the nutritional adequacy of foods in the lunch boxcurrently supplied by their mother. It aims to give the knowledge & ideaabout the quality and the quantity of the foods in the lunch box. The study wasa cross-sectional survey carried out in all full day primary schools inMuzaffarnagar District. Lunch boxes samples from each participating schoolswere collected. The different food group such as cereal product, vegetable,meat and milk product in the lunch box was included to access the nutritionalstatus of the foods in the lunch box of pre-school children. Different cookingmethod was also used to assess the nutritional status of lunch boxes of primaryschool children. This Studies shows that7% like roasted method to prepare foodfor lunchbox, 13% like boiling method, 56% like deep frying method whereas 24%like other methods to prepare food for lunchbox. For the cooking methods of foods in the lunch box, thecommonest cooking methods for cereal and vegetable was boiling and steaming.But most of the mother like fried and deep fried cooking method for theirchild because their child like fried food lunch contribute about one third ofdaily energy intake for primary school students. If the nutritional value doesnot meet with the recommended value, it will predispose to childhood obesity.Therefore, appropriate health promotion programmed on healthy lunch box, inparticular on the promotion of correct quality& quantity of the foods,should be implemented.